Carbon tetrachloride-induced acute liver toxicity: selecting dosage and biomarkers for evaluating hepatoprotective drugs in ICR outbred mice - Theerut Luangmonkong; Chanitkarn Pransin; Ladawan Nopphalee; Sirada Meechai; Suprawee Chunya; Atis Rattanavaraha; Naphat Kaewnoppharat; Thayida Khuituan; Sanpetch Bunyakiat; Warisara Parichatikanond (Faculty of Pharmacy, Mahidol University, 2022)
Evaluating effects of putative chemical or herbal agents against a single intraperitoneal administration of carbon tetrachloride (CCl4) in rodents is a widely used model for studying hepatoprotective potency. Since the toxic effects of CCl4 is dependent on individual species; therefore, our study aimed to demonstrate a procedure to select the optimal dosage of CCl4 and types of liver damage-associated biomarkers for testing hepatoprotective drugs in ICR mice. To include inter-individual genetic variation, the test was conducted in outbred mice. Silymarin and rebamipide were applied as the representative tested agents. We revealed that 15-150 µL/kg of CCl4 induced liver damage including hepatocyte vacuolation and ballooning with infiltration of inflammatory cells, centrilobular necrosis, and increased serum alanine aminotransferase and aspartate aminotransferase, in a dosage-dependent manner. Nonetheless, serum levels of bilirubin were not significantly increased at 15 µL/kg of CCl4. On the other hands, the level of alkaline phosphatase was not parallel with the increased dosage of CCl4. Most importantly, as observed using liver histology and serum biomarkers, rebamipide and silymarin showed hepatoprotective effects against 15 µL/kg of CCl4 merely, whereas both drugs were unable to protect liver injury against 150 µL/kg of CCl4. In conclusion, this study demonstrated how to design an experiment to select the optimal dosage of CCl4for evaluating hepatoprotective effects of putative agents in a specific tested species. In addition, we revealed choices of serum biomarkers which could be associated with the severity of liver damage.